Cutaneous manifestation of leukaemia on the penis—the possible implications. Issue 12 (31st December 2020) - Ng, Angela; Gurun, Murat
Abstract: Skin lesions are common in the patients with chronic lymphoid leukaemia (CLL); however, leukaemia cutis is a cutaneous manifestation secondary to any form of leukaemia and generally an uncommon phenomenon. They typically present on the face and neck as well as exposed areas. Our case looks at a 78-year-old gentleman with known CLL who presented with an asymptomatic raised lesion in his inner prepuce. The lesion was excised and his immunohistology staining confirms expression of CD5, CD20 and CD23 that is consistent with cutaneous manifestation of CLL. This case highlights the importance of taking leukaemia cutis into consideration in patients with known CLL with unusual features.